Food, rural, agricultural and fisheries policies in Malta - Attard G.; Meli A. (Les agricultures méditerranéennes : analyses par pays, 2008)
In 1992 a comprehensive study entitled Malta Agricultural Policy and EC Membership: Challenges and Opportunities was conducted by FAO and presented to Government of Malta. This project had the objective of carrying out an agricultural sector review aimed at the implementation of the new international and domestic policy changes necessary for eventual EU membership. This report made particular emphasis on the proposal for dealing with key agricultural policy deemed to be crucial for the survival of the sector. Despite that a certain degree of restructuring and amelioration has occurred, the agricultural sector in Malta has not reversed its long-term decline, nor does it appear to have attained sustainability. Furthermore, the Maltese structural and geographical features of the territory are not so conducive to investment, and are, in part, responsible for imparting a dampening effect on investment potential. Nonetheless issues of markets, production organization and policy have a significant role. The lack of efficiently functioning markets for outputs as well as inputs; conservative attitudes in the sector towards modern, efficient and effective business practices; the pattern of land ownership and tenure, that curtails productivity and the entry of new operators into the sector; these all act together to create a complex matrix within which investment has its limitations. To further complicate these issues, the sector has no clear long term policy direction, thus resulting in uncoordinated actions in terms of effort, time and investments towards established goals. The objective of this paper is to portray the developments in the Maltese agro-food sector in conjunction with related policy changes.